DAMPAK PEMEKARAN TERHADAP PEMBANGUNAN DAERAH DI KECAMATAN PEKAITAN KABUPATEN ROKAN HILIR TAHUN 2010-2012 - Andi Rakasiwi; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
service to the community. With the expansion in the area expect an every community needs thatmust be fulfilled by the government can be identified and coordinated in accordance with theirrespective potentials. However, if viewed from the concept, the role of local government is toprovide public services. Accompanying the political dynamics that have developed since thebeginning of the reform era, especially with regard to the enactment of Law No. 22 of 1999sprung the desire of various regions to split away to form new autonomous regions. For thegovernment issued Government Regulation No. 129 of 2000 on Regional Expansion governing,among others, about the procedural instruments and instrument requirements of regionalexpansion. and Government Regulation (PP) No. 19 of 2008 on government enacted the District.The main purpose Pekaitan the District Redistricting is "to improve services andaccelerate development. Expansion of the District Pekaitan also expected to create localindependence and improve the welfare of the community "through: (1) improvement of serviceto the community; (2) accelerating the growth of democracy; (3) accelerating the implementationof regional economic development, (4) acceleration potential management areas, (5) increasedsecurity and order.This study is a qualitative research, the data collection techniques in this study is adescriptive analysis. This study uses in-depth interviews with informants who did understand theresearch problems that become the object of information, and documentation study aimed toobtain information in the study.The purpose of this study is: (1) To describe the impact of the expansion of the subdistrictin the district Pekaitan regional development and the impact of the expansion of publicservices in the District Pekaitan. This study is a qualitative research technique used to collectdata Descriptive AnalysisThe results showed that: 1) positive and negative impacts on development PekaitanRokan Hilir Subdistrict. 2) positive and negative impacts on public services in the District ofRokan Hilir Pekaitan.Keywords: Impact of Redistricting Districts, Development